Sistem Informasi Bimbingan Konseling Berbasis Web Pada SMP Negeri 4 Batang Anai: - Arman, Arman; Nelfira, Nelfira; Dilson, Dilson; Sotar, Sotar; Afdal , Rifki Afdal (SMART : Jurnal Teknologi Informasi dan Komputer, 2023)
This study aims to design a counseling guidance information system to assist BK teachers in providing guidance and counseling to their students in improving morals and behavior. The problem with the manual system used by schools is the difficulty of managing violations recorded in case notebooks and reports which are still less effective and efficient. The method in designing this web-based system uses the waterfall method as a system development tool with UML design tools. The results of this study are in the form of a counseling guidance information system that can facilitate BK teachers in managing student behavior and morals and parents can monitor their child's development in the system. In addition, reports that are designed can display students' behavior and morals in detail.